MENINGKATKAN MOTIVASI BELAJAR MENULIS HURUF DEWANAGARI MELALUI METODE DEMONSTRASI DI SDN TULUNGREJO 02 KECAMATAN BUMIAJI KOTA BATU - Made Dwiana Mustawan (Widya Aksara, 2020)
Education is a process of growth. Learning methods have a big enough share in teaching and learning activities. The ability that is expected to be possessed by students, will be determined by the relevance of the use of a method in accordance with the objectives. The implementation of learning in schools, especially Hindu religious education at SDN Tulungrejo 02, Bumiaji Subdistrict, Batu City, grade 1 to grade 3, additional material for writing the letters of the Islamic Board of Education is less attractive to students. From the background of the problem, the formulation of the problem in the discussion of the material above is as follows: (1) How is the teaching and learning process of writing the Dewanagari letters in SDN Tulungrejo 02 Bumiaji Subdistrict Batu City ?, (2) What is the motivation for learning to write the Dewanagari letters of Hindu class students 1 to 3 with the Demonstration learning method being applied at SDN Tulungrejo 02 Bumiaji District, Batu City. From the results of this study the data obtained students were only able to recognize and write the council letters about 10.2-12 letters from a total of 45 letters that are usually taught. And the percentage of students' ability to recognize letters is no more than 25-27% with less criteria. After taking action in the first cycle, there was an increase in the ability to recognize and write the council letters, although there has not been a significant difference. In grade 1 to grade 3 students of SDN Tulungrejo 02 Bumiaji Subdistrict Batu city were given 15 questions at the first meeting to the third meeting in the first cycle and the results were that the average student was able to answer an average of 3 questions at the first meeting, 3 questions at the second meeting, 5 at the third meeting so that the results of the percentage of the ability to recognize and write the councilors in the learning groups of students in grades 1 to 3 are not more than 36.7%. While at the end of the first cycle meeting 45 questions were given and the average student was only able to write 10 questions with a percentage of students' abilities of 45%. The study group consisted of grades 1 to grade 3 given 15 questions in the first meeting to the third cycle II and the results were the average student was able to answer 9 questions at the first meeting 11 questions at the second meeting 14 questions at the third meeting and at the end of the evaluation 45 questions then the average student is able to answer 33 questions with a large percentage of 74% Based on the graphic data, it is clear that there was a significant increase in motivation to write Dewanagari letters in students at SDN Tulungrejo 02, Bumiaji District, Batu City. The process of introducing and writing the council letters with the demonstration method gives good results for students of SDN Tulungrejo 02 Bumiaji District, Batu City.